TEACHING STUDENTS THE ART OF EMBROIDERY AND ARTISTIC WEAVING IN EXTRACURRICULAR ACTIVITIES - Mukumova , Feruza; Baymurova , Nigora (Универсальная индексная библиотека Евразийского журнала социальных наук, философии и культуры, 2023)
The article provides samples of embroidery and artistic weaving of the Uzbek people. Methods for making jewelery and drawings are beingstudied, the thread is used, the fabrication is made from homemade cotton and cotton, the author gives the names of objects insufficient quantities that have survived in the oral speech of the local population of the Surkhan oasis. The traditional importance of weaving, embroidery in the life of young people.